SPECIFIC ASPECTS OF COMMERCIALIZATION OF SCIENTIFIC RESEARCH RESULTS AND IMPLEMENTATION OF INNOVATION ACTIVITIES (Universal International Scientific Journal, 2026)
This scientific article analyzes the theoretical foundations of commercialization ofresearch results, modern forms of innovative activity (startups, technology transfer, implementation ofscientific developments into production), existing systemic problems, and specific proposals andsolutions aimed at addressing them based on a comprehensive approach
Keywords: commercialization; innovation; startup